2021
DOI: 10.1111/apt.16621
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic gastritis and its relationships with other gastrointestinal disorders

Abstract: Background: Lymphocytic gastritis (LyG) is a histopathologic finding of unknown clinical relevance.Aims: To explore the clinical epidemiology of LyG and its associations with Helicobacter pylori (Hp) infection, coeliac disease (CD) and microscopic colitis (MC) Methods: In a cross-sectional study, the demographic, clinical, and histopathologic data of patients with and without LyG were compared. Between 2008 and 2020, 1.5 million patients with endoscopic biopsies of the gastroduodenal mucosa were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…LG has been found in association with a variety of disorders, such as coeliac disease, H pylori gastritis, HIV, Meanetrier's disease, NSAIDs, and also with angiotensin II receptor blockers suggesting an abnormal local immunologic response to different antigens as the underlying pathophysiologic mechanism (98,99). A recent large retrospective study in adults has, however, questioned the pathogenic role of H pylori infection (100). The prevalence of LG in children with coeliac disease ranges between 10% and 45% (101–105).…”
Section: Resultsmentioning
confidence: 99%
“…LG has been found in association with a variety of disorders, such as coeliac disease, H pylori gastritis, HIV, Meanetrier's disease, NSAIDs, and also with angiotensin II receptor blockers suggesting an abnormal local immunologic response to different antigens as the underlying pathophysiologic mechanism (98,99). A recent large retrospective study in adults has, however, questioned the pathogenic role of H pylori infection (100). The prevalence of LG in children with coeliac disease ranges between 10% and 45% (101–105).…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytic gastritis is characterized by non‐specific clinical manifestations, with common symptoms such as dyspepsia, epigastric pain, heartburn, vomiting, and weight loss. It is closely associated with H. pylori infection, and some patients may have concomitant celiac disease 63,64 …”
Section: Clinical Issues and Statementsmentioning
confidence: 99%
“…H. pylori infection, and some patients may have concomitant celiac disease. 63,64 Mild granulomatous gastritis is asymptomatic. However, when the lesion is large, patients may develop gastric ulcers or evacuation disorder, leading to epigastric pain, abdominal distension, nausea, vomiting, gastrointestinal bleeding, and anemia.…”
Section: Patients With Aig Do Not Have Any Typical Clinical Manifesta...mentioning
confidence: 99%
“…Whereas it is not a specific disease group, it is usually seen in coincidence with other lymphocytic disorders and is closely associated with MC [ 73 , 81 ]. A cross-sectional study including 3,038 patients with LyG reported that 19% of patients can develop MC as a co-morbidity [ 82 ]. DIL is the most common lymphocytic disorder of the gastrointestinal tract.…”
Section: Relationship Between MC and Other Lymphocytic Disorders Of T...mentioning
confidence: 99%